2018
DOI: 10.1055/s-0038-1673636
|View full text |Cite
|
Sign up to set email alerts
|

Regular Physical Activity and Risk of Venous Thromboembolism

Abstract: Venous thromboembolism (VTE) is a complex multifactorial disease that represents a growing public health concern. Identification of modifiable risk factors at the population level may provide a measure to reduce the burden of VTE. In this review, we summarize current knowledge of the role of physical activity on the risk of VTE and VTE-related complications.We also discuss methodological challenges related to research on physical activity, and put forward plausible mechanisms for an association between physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…Though there has been overwhelming evidence showing that regular physical activity is associated with reduced risk of arterial thrombotic disease [1][2][3], findings on the relationship between physical activity and VTE risk have been mixed in the absence of a pooled analysis. In a recently published narrative review that evaluated the existing epidemiological evidence on the association between physical activity and VTE risk, Evensen and Table 1 colleagues concluded that there might be a modest beneficial effect of physical activity on incident VTE risk [34]. However, the evidence was hampered by the variance in the assessment and definition of the exposure variablephysical activity.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there has been overwhelming evidence showing that regular physical activity is associated with reduced risk of arterial thrombotic disease [1][2][3], findings on the relationship between physical activity and VTE risk have been mixed in the absence of a pooled analysis. In a recently published narrative review that evaluated the existing epidemiological evidence on the association between physical activity and VTE risk, Evensen and Table 1 colleagues concluded that there might be a modest beneficial effect of physical activity on incident VTE risk [34]. However, the evidence was hampered by the variance in the assessment and definition of the exposure variablephysical activity.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…Some studies have reported decreased VTE risk with increased physical activity [26][27][28], whereas others have shown increased VTE risk with increased physical activity [29,30] or no significant evidence of associations [31][32][33]. In a recent narrative review of existing observational prospective evidence, the authors evaluated and concluded that there may be a small beneficial effect of physical activity on the risk of incident VTE, but this did not appear to be consistent with a dose-response relationship [34]. A number of randomised controlled trials and observational studies have assessed the benefits and risks of physical activity on VTE, but these were based in patients or populations with acute or previous DVT [35].…”
Section: Introductionmentioning
confidence: 99%